Low Alcohol and Cigarette Use Is Associated to the Risk of Developing Chronic Pancreatitis. Issue 2 (February 2017) - Di Leo, Milena; Leandro, Gioacchino; Singh, Satish K.; Mariani, Alberto; Bianco, Margherita; Zuppardo, Raffaella Alessia; Goni, Elisabetta; Rogger, Teresa Marzia; Di Mario, Francesco; Guslandi, Mario; De Cobelli, Francesco; Del Maschio, Alessandro; et al.
Abstract : Objectives: The aim of this study was to investigate the contribution of smoking and alcohol intake and pancreas divisum on the risk of developing chronic pancreatitis (CP). Methods: Consecutive patients with CP who underwent secretin-enhanced magnetic resonance cholangiopancreatography were compared with consecutive patients without pancreatic disease who underwent secretin-enhanced magnetic resonance cholangiopancreatography for irritable bowel syndrome. Results: We enrolled 145 consecutive CP patients and 103 irritable bowel syndrome patients from 2010 to 2014. In a univariate analysis, statistically significant differences in sex, mean age, and the duration and amount of cigarette and alcohol use were found. Per a receiver operating characteristic curve analysis, thresholds for cigarette and alcohol consumption were, respectively, 5.5 cigarettes and 13.5 g daily. In a multivariate analysis, independent risk factors for CP were male sex (odds ratio [OR], 2.05), smoking more than 5.5 cigarettes per day (OR, 2.72), and drinking more than 13.5 g/d (OR, 6.35). Conclusions: In an Italian population, we confirmed smoking and alcohol as cofactors in the development of CP. This study shows that alcohol intake and smoking habits are 2 of the most important risk factors for the development of CP.